Integrity breaches in a hollow fiber nanofilter – Effects on natural organic matter and virus-like particle removal. (15th November 2016) - Lidén, Angelica; Lavonen, Elin; Persson, Kenneth M.; Larson, Magnus
Abstract: Ultrafiltration and nanofiltration have become common methods to treat surface water for drinking water purposes. Common aims of a membrane step are removal of natural organic matter (NOM), softening or adding an extra microbiological or chemical barrier. In most cases, the membrane is considered a good disinfection step; commonly the viral removal is at least 4–log. To ensure a working disinfection, reliable integrity tests are required. In the present pilot study with a hollow fiber nanofilter, the membrane achieved a high NOM reduction, and the difference in parameters related to NOM quality before and after treatment proved to be useful indicators of integrity breaches. Changes in total organic carbon (TOC) concentration, UV-absorbance at 254 nm (UVA254 ) and fluorescence derived parameters in the permeate flow were related to leaking fibers. On average, UVA254 in the permeate was 3 times higher for a membrane with compromised fibers (0.041 cm −1 ) compared to an intact membrane (0.013 cm −1 ), while TOC was less than 2 times as high on average. Thus, this membrane had a higher reduction of UVA254 than TOC and the sensitivity for changes from leakage was higher. Therefore, it is suggested that UVA254 could be used as an indicator for membrane integrity. Additionally, there is a significant (P < 0.01) difference in fluorescence derived parameters between a leaking and an intact fiber, showing that fluorescence also has potential to be applied for online monitoring of membrane processes. During fiber failure, around 2% of the permeate flow passes through one single leaking fiber. The transport depends on the distance between the inflow and the leak, which in most cases are similar and most likely close to the middle of the fiber. Highlights: UV-absorbance at 254 nm can be used for indirect integrity monitoring. The fluorescence derived parameters could detect a leaking fiber. Leakage most likely occurred in the middle of the fibers. Ca 2% of the permeate flow from a compromised module passes through a leaking fiber.